Improved SLM algorithm for PAPR reduction in OFDM system - Ce JI; Wenjing ZHU; Ying WEI; Dianxia JIA (Tongxin xuebao)
In order to reduce the peak to average power ratio (PAPR) of the conventional selective mapping (SLM) algorithm,decrease the transmission of side-band information,and improve the spectral efficiency in the orthogonal frequency division multiplexing (OFDM) system,the TL-SLM algorithm based on the conversion matrix and the chaotic sequence was proposed firstly.Although the TL-SLM algorithm could effectively decrease the transmission of side-band information,the reduction of PA P R was limited.To solve this problem,an improved TL-SLM algorithm based on the rotation vector was proposed,which was the TR-SLM algorithm.TR-SLM algorithm introduced the rotation vector to generate more time-domain alternative signals to further reducing the PA P R.The performance analysis shows that although the TL-SLM algorithm and the TR-SLM algorithm increase the complexity a little,the PA P R performance is effectively improved and the transmission of side-band information is greatly reduced.